The middle kingdom in Africa: a quantitative study of support for the China model - Bentzen, Joachim (Department of Political Studies, 2016)
This paper provides a quantitative empirical study of support for the China model in Africa. Using comprehensive and previously unpublished data from Afro barometer's sixth round (2014-2016) the paper offers the first large-n (n= 46741) multicounty (n=31) empirical evaluation of support for the Chinese model of development. The paper is structured around two research questions. First, what is the rate of preference in Africa for the China model? Second, what are the determinants that underlie this preference? The China model is a contested construct. An extended literature review is therefore employed to establish where the construct fits within existing literature and then identify the key features that can be measured by my model. The pursuing analysis has two main sections; one descriptive and one explanatory. The descriptive section seeks to establish what the rate of support for the China model is in Africa. This section also provides a summary of sentiments in Africa towards the Chinese engagement. This summary of sentiments is included for two reasons. Firstly, because no consensus exists on the tonality of sentiments towards China in Africa this topic is of interest in and of itself. Secondly, because, as the model will show, these attitudes are intimately linked to respondent likelihood of choosing the China model for development. The explanatory section utilizes a multilevel regression model to explore why Africans pick the Chinese model over other development models. The regression employs a broad set of variables on individual priorities for development, values on democracy and views on the Chinese engagement in the respondents own country. At the national level the model includes measures on country characteristics such as development level and regime type. The model also investigates the effect of an aggregate Chinese 'footprint' in individual African nations. This footprint consists of Chinese trade, foreign direct investment and development assistance. The data on Chinese FDI and AID is collected from innovative open-source research projects based in the United States. The paper finds considerable support for the China model in Africa. China was the second most popular choice of development model after the United States. In ten of the surveyed countries it was the dominant choice. The descriptive section finds that Africans are on average positive towards the Chinese engagement on the continent. The multilevel regression model finds that respondents who offer positive evaluations of China's engagement in their own country are much more likely to choose the Chinese model for development. Individual values on democracy and individual preferences on development are not found to influence choice of development model. The likelihood of respondents choosing the Chinese model decreases as a country's level of development increases. Respondents nested within freer societies are, surprisingly, more likely to choose the Chinese model of development. Increased Chinese presence in the form of aid and foreign direct investment is found to make respondents less likely to choose the China model. While increased imports from China increases the chance that respondents will choose China as their model for their country's development.